Melatonin Regulates the Periodic Growth of Cashmere by Upregulating the Expression of Wnt10b and β-catenin in Inner Mongolia Cashmere Goats - Liu, Junyang; Mu, Qing; Liu, Zhihong; Wang, Yan; Liu, Jiasen; Wu, Zixian; Gong, Wendian; Lu, Zeyu; Zhao, Feifei; Zhang, Yanjun; Wang, Ruijun; Su, Rui; et al. (Frontiers in Genetics, 2021)
Secondary hair follicle growth in cashmere goats has seasonal cycle changes, and melatonin has a regulatory effect on the cashmere growth cycle. In this study, the growth length of cashmere was measured by implanting melatonin in live cashmere goats. The results indicated that the continuous implantation of melatonin promoted cashmere to enter the anagen two months earlier and induce secondary hair follicle development. HE staining of skin tissues showed that the number of secondary hair follicles in the melatonin-implanted goats was significantly higher than that in the control goats (P<0.05). Transcriptome sequencing of the skin tissue of cashmere goats was used to identify differentially expressed genes: 532 in February, 641 in October, and 305 in December. Fluorescence quantitative PCR and Western blotting results showed that melatonin had a significant effect on the expression of Wnt10b, β-catenin and proteins in the skin tissue of Inner Mongolia cashmere goats. This finding suggested that melatonin alters the cycle of secondary hair follicle development by changing the expression of related genes. This research lays the foundation for further study on the mechanism by which melatonin regulates cashmere growth.